Threat of scrub typhus in post-earthquake Nepal - Thapa, S; Sapkota, L B; Hamal, P (Journal of Chitwan Medical College, 2017)
Scrub typhus is a potentially fatal zoonotic infection, reported from many parts of Asia including Nepal. There is increasing reports of outbreak of Scrub typhus, after the earthquake hit Nepal on April 25, 2015. The recent outbreak of Scrub typhus posed problems in diagnosis and treatment of the disease. It may be related to poor awareness of the disease or lack of suspicion for Scrub typhus which often presents with clinical features indistinguishable from typhoid fever. Since, various parts of Nepal appeared to be suitable hubs for Scrub typhus, the clinical suspicion of Scrub typhus in the differential diagnosis of fever of unknown origin (FUO) is of utmost importance to prevent mortality and morbidity. This is a prospective study conducted in Chitwan Medical College (CMC), Chitwan, Nepal. This study was carried out over a period of 4 months extending from June 2016 to September 2016. A total of 410 serum samples were collected from all patients visiting CMC, clinically suspected of having Scrub typhus infection. The samples were processed for the detection of IgM antibodies for Scrub typhus by ELISA. Results: A total of 410 samples from patients suspected with Scrub typhus infection were processed which included 200 males and 210 females. Out of total 410 samples tested, 181 (44.1%) were seropositive for Scrub typhus. Seropositivity was highest 25.9% among the age group 11-20 years of age. Females were infected more than males. This study implies the re-emergence of Scrub typhus in different regions of Nepal. Although the disease is endemic in our country, it is grossly underdiagnosed owing to non-specific clinical presentation and lack of diagnostic facilities. It is thus suggested that high index of suspicion should be maintained for cases presenting with febrile illness. Infection with Scrub typhus was found high and this calls for an urgent need to introduce vaccine against Scrub typhus.